Predicting Juvenile Reentry Success: Developing a Global Risk Score and Risk Classification Levels Using the Residential Positive Achievement Change Tool - Baglivio, Michael T. (Youth violence and juvenile justice, 2019)
Recent decades have seen the proliferation of risk assessment implementation and, subsequently, validation studies. Most assessments are used at the front end, at arrest or postdisposition for juvenile offenders. The current study develops an overall risk score and risk classification levels from a tool developed specifically for use with youth within residential placement in efforts to predict reentry success. A diverse, 4-year statewide sample of serious juvenile offenders (N = 15,078) is examined. The total risk score and classification schematic development are outlined, predictive validity assessed, and the ability of the classification to partition youth into meaningful subgroups of overall risk to reoffend analyzed. Results show predictive validity on par with prominent juvenile tools, which is noteworthy given the sample exclusivity: serious offenders in residential placement. Further, the tool classifies youth into five distinct groups with meaningful dispersion across groups with differing recidivism base rates. Implications for juvenile reentry are discussed.